2022
DOI: 10.3390/toxics10120722
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics and Source-Specific Health Risks of the Volatile Organic Compounds in Urban Nanjing, China

Abstract: This work comprehensively investigated the constituents, sources, and associated health risks of ambient volatile organic compounds (VOCs) sampled during the autumn of 2020 in urban Nanjing, a megacity in the densely populated Yangtze River Delta region in China. The total VOC (TVOC, sum of 108 species) concentration was determined to be 29.04 ± 14.89 ppb, and it was consisted of alkanes (36.9%), oxygenated VOCs (19.9%), halogens (19.1%), aromatics (9.9%), alkenes (8.9%), alkynes (4.9%), and others (0.4%). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…In this work, we further improved this method and for the first time, applied it to directly quantify the ALWC in ambient PM 2.5 in Nanjing during the summer of 2023. Our findings are also insightful for our understanding of ambient aerosol chemistry and toxicology in similar large cities like Nanjing with relatively significant air pollution issues [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 79%
“…In this work, we further improved this method and for the first time, applied it to directly quantify the ALWC in ambient PM 2.5 in Nanjing during the summer of 2023. Our findings are also insightful for our understanding of ambient aerosol chemistry and toxicology in similar large cities like Nanjing with relatively significant air pollution issues [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 79%
“…The current study provides useful insights for a better understanding of the exposure levels to benzene and the associated health impact in Ploieşti, despite the limitations determined by the data hiatus and incomplete or missing information regarding the health impact. Future work will consider an assessment of the multipollutant effects on health by including other VOCs in the analysis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The LCR value indicates the probability of cancer occurrence and is usually expressed in terms of the number of individuals with cancer in a certain population. For example, the carcinogenic risk value is 10 −6 -10 −4 , that is, one cancer patient will be added for every 10,000 to 1 million people [24]; HQ is the value obtained by dividing the average exposure concentration by the reference concentration, indicating the maximum amount of pollutants that will not cause adverse reactions in the human body ingested per unit weight per unit time. The average daily dose of any compound (E D , mg•kg −1 day −1 ) was calculated using Equation (1) [25].…”
Section: Health Risk Calculationmentioning
confidence: 99%
“…However, some researchers have found that compounds with non-carcinogenic risks higher than 0.1 may also have potential non-carcinogenic risks [30]. For cancer risk, a compound with a risk value >1.0 × 10 −4 is considered an "identified risk", a compound with a risk value between 1.0 × 10 −5 and 1.0 × 10 −6 is a "possible risk", and a compound with a risk value less than 1.0 × 10 −6 is a negligible risk [24]. Species with potential risks were also presented in this study.…”
Section: Health Risk Calculationmentioning
confidence: 99%